Cauda equina nerve root enhancement in adult intestinal toxemia botulism - Jiang, Ruiji; Beland, Benjamin; Shah, Vinil; Kang, Min; Pet, Douglas B. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Adult botulism is a rare, life-threatening condition typically caused by exposure to preformed botulinum neurotoxin (BoNT). Acute intestinal toxemia botulism (AITB) is an uncommon subtype resulting from colonization of Clostridium botulinum in the intestines. Diagnosis is made by detecting BoNT in the patient’s blood, stool, or gastric fluid. AITB is confirmed when C. botulinum is isolated in culture. Electrodiagnostic studies may support the diagnosis, while imaging—when performed—is generally used to exclude alternative conditions. Case presentation A 74-year-old man presented with acute dysarthria and ophthalmoparesis, which rapidly progressed to quadriparesis and respiratory failure requiring intubation. Magnetic resonance imaging (MRI) revealed thickening and enhancement of the cauda equina nerve roots. Due to high clinical suspicion for botulism, heptavalent botulinum antitoxin was administered. Intravenous immunoglobulin was also given, as the imaging findings raised concern for an alternative diagnosis of Guillain-Barré syndrome (GBS). Blood and stool samples later tested positive for BoNT type A, and C. botulinum was isolated from the stool, confirming AITB. The patient experienced a gradual but prolonged recovery of motor function following treatment. Conclusions Botulism in both infants and adults is not typically associated with abnormal neuroimaging findings. To our knowledge, this is the first reported case of cauda equina nerve root thickening and enhancement on MRI in AITB—or in adult botulism more broadly. We outline the differential diagnosis, pathophysiology, and treatment of botulism. This case underscores that abnormal neuroimaging should not delay prompt empiric treatment for botulism when clinical suspicion is high.